2017
DOI: 10.1159/000481088
|View full text |Cite
|
Sign up to set email alerts
|

Shift Work and the Risk of Coronary Artery Disease: A Cardiac Computed Tomography Angiography Study

Abstract: Aims: Shift work disrupts the normal circadian rhythm and is associated with risk factors for coronary artery disease (CAD) and a higher incidence of CAD morbidity and mortality. Cardiac computed tomography angiography (CCTA) is a robust noninvasive modality for assessing the presence, extent, and severity of CAD. We sought to investigate whether shift workers are prone to a higher burden of CAD compared to non-shift workers. Methods: We conducted a historically prospective study in consecutive patients who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 13 publications
0
8
0
2
Order By: Relevance
“…A longitudinal population-based study reported that a lower robustness of the rhythm and a lower amplitude were associated with an increased risk of overall cardiovascular disease, and that a lower mesor was associated with an increased risk of coronary heart disease [70•]. It has also been repeatedly shown that shift work is a risk factor for cardiometabolic disease, such as type 2 diabetes, obesity, and coronary artery disease [50,71,72]; the 24-h activity rhythm has however not been assessed in these studies. Most of these findings have been based on observational studies, making it difficult to determine the underlying mechanisms.…”
Section: Cardio-metabolic Diseasementioning
confidence: 99%
“…A longitudinal population-based study reported that a lower robustness of the rhythm and a lower amplitude were associated with an increased risk of overall cardiovascular disease, and that a lower mesor was associated with an increased risk of coronary heart disease [70•]. It has also been repeatedly shown that shift work is a risk factor for cardiometabolic disease, such as type 2 diabetes, obesity, and coronary artery disease [50,71,72]; the 24-h activity rhythm has however not been assessed in these studies. Most of these findings have been based on observational studies, making it difficult to determine the underlying mechanisms.…”
Section: Cardio-metabolic Diseasementioning
confidence: 99%
“…Experimental studies have been carried out on animals that show that prolonged CR misalignment between the body and the external environment is a risk factor for heart disease, as the heart is no longer protected from injury [18]. In the morning, fibrinolysis decreases and heart rate, blood pressure, platelet reactivity, vasoconstriction and intra-arterial pressures increase, after the night-time dip.…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…A rotating day/night shift work system puts strain on the body and disturbs the functioning of defense mechanisms. Exposure to negative factors may contribute to a higher incidence of health problems [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…System, w którym występują naprzemiennie zmiany nocne oraz dzienne trwające dwanaście godzin jest podstawową formą zatrudnienia personelu pielęgniarskiego [2]. W literaturze przedmiotu przedstawiane są liczne doniesienia wskazujące na niekorzystny wpływ pracy zmianowej na organizm ludzki, który zwiększa ryzyko wystąpienia schorzeń układu krążenia, układu pokarmowego, zaburzeń snu, zaburzeń neuropsychiatrycznych oraz dolegliwości bólowych [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Negatywne czynniki środowiskowe i zmianowy system pracy mogą również znacząco wpływać na stan zdrowia personelu pielęgniarskiego.…”
Section: Wprowadzenieunclassified
See 1 more Smart Citation